دراسة أثر التمويل الإسلامي في البورصة الماليزية على النمو الاقتصادي باستخدام منهجية اختبار الحدود ARDL: Studying the Impact of Islamic Finance in Malaysian Stock Exchange on Economic Growthusing the ARDL Bound Test Methodology - عيسى نجاة (Journal of North African Economies, 2025)
Islamic finance has recently witnessed remarkable global interest, particularly the Islamic stock exchange market in Malaysia, for its years of success at the macroeconomic level. The desire for this research paper led us to explore this pioneering experience in employing this type of finance that has contributed to Malaysia's development renaissance, through two themes, the first of which highlighted the role of Islamic finance in achieving economic growth through principles and tools that encourage wealth-producing investment and create growth. In the second axis, we used econometric modeling to study the impact of two variables of stock market which are sukuk volume and Islamic market value on GDP, to reveal the nature of the relationship between them using the ARDL boundary test model and the error correction model with "R" program and its statistical packages.